Fabrication of CZTS Films through a Combined Electrodeposition and Solution Process: An Experimental and First‐Principles Study - Prof. Ramazan Katirci; Mehmet Nurullah Onel; Ilhan Danaci; Kevser Irem Danaci; Dr. Salih Ozbay; Dr. Fuat Erden (ChemElectroChem, 2023)
Abstract Sulfurization has a critical role in preparation of CZTS films since the main drawback of CZTS is due to the presence of S‐based impurities. In general, sulfurization could be performed during or following annealing, or the entire CZTS structure could be prepared through sol‐gel. However, toxic gases are used for the former, and the latter takes prolonged times. Alternatively, a combined electrodeposition and solution process was proposed in the present work to prepare CZTS. Briefly, we electrodeposited CZT layers on a metal substrate, and then immersed the as‐prepared coating in a S containing solution for the sulfurization. The effects of electrodeposition time, electrodeposition order, current density, electrolyte compositions, sulfurization time, and annealing pressure were studied. Overall, the results show that S content of the films varied between 27 and 52 % depending on process parameters, thus, suggesting the effectiveness of the proposed approach regarding sulfurization. However, various secondary phases were also detected as well as considerable amount of oxygen impurity. Accordingly, we opted for a computational approach to elucidate the effect of oxygen impurities, and report that the band gap of the films varied between 0.59 and 0.05 eV depending on the presence and which sites oxygen atoms occupy.